Biochemical Modulation of Lipid Pathway in Microalgae Dunaliella sp. for Biodiesel Production. (3rd June 2015) - Talebi, Ahmad Farhad; Tohidfar, Masoud; Mousavi Derazmahalleh, Seyedeh Mahsa; Sulaiman, Alawi; Baharuddin, Azhari Samsu; Tabatabaei, Meisam
Abstract : Exploitation of renewable sources of energy such as algal biodiesel could turn energy supplies problem around. Studies on a locally isolated strain of Dunaliella sp. showed that the mean lipid content in cultures enriched by 200 mg L −1 myoinositol was raised by around 33% (1.5 times higher than the control). Similarly, higher lipid productivity values were achieved in cultures treated by 100 and 200 mg L −1 myoinositol. Fluorometry analyses (microplate fluorescence and flow cytometry) revealed increased oil accumulation in the Nile red-stained algal samples. Moreover, it was predicted that biodiesel produced from myoinositol-treated cells possessed improved oxidative stability, cetane number, and cloud point values. From the genomic point of view, real-time analyses revealed that myoinositol negatively influenced transcript abundance of AccD gene (one of the key genes involved in lipid production pathway) due to feedback inhibition and that its positive effect must have been exerted through other genes. The findings of the current research are not to interprete that myoinositol supplementation could answer all the challenges faced in microalgal biodiesel production but instead to show that "there is a there there" for biochemical modulation strategies, which we achieved, increased algal oil quantity and enhanced resultant biodiesel quality.